Investigating the Feasibility of Using Cassava Starch as a Partial Replacement of Cement Used in Mortar: A Case Study Moyo District (Palorinya Refugee Settlement Camp). - Ongom, Samuel (Kabale University, 2025)
The cost of building materials i.e. lake sand, cement, lime, and steel are high and rising and is also becoming scarce, as a result of these, the cost of building construction is ever increasing. Cement and lime production emits greenhouse gases that deplete the ozone layer, resulting in environmental problems. Consequently, people in the villages have resorted to using Cassava mortar to save money. Given the low-income level of the population, many cannot afford decent housing since costs have risen and continue to rise from 20,000ugx in early 2001 to 40,000ugx today for a bag of 50kg cement from the West Nile region and a 20kg bag of lime from 5000ugx previously to 12,000ugx currently. In real terms, the income levels are still very low and poverty levels are 41.7% of the population. However, engineers, construction managers, and relevant stakeholders have not embraced the use of cement Cassava starch mortar mix to bond the bricks because they do not know the performance of the brick wall constructed with the mortar mix of Cement Cassava Starch. Therefore, there is a need to investigate the strength of cassava starch mortar, compared to cement mortar because this will greatly reduce the cost of construction and impact positively on the environment.